ENT 300 : Currybang House / Syamsury Umar... [et.al] - Umar, Syamsury; Fadzil, Noor Farina; Isik, Chris Herbert; Baral, Puyang (2008)
There are criteria and conditions that have t be fulfilled which require the involvement of effort and precision of producing our goods. Without such conditions, the business cannot run properly and organizational goals will no be achieved. These conditions must be achieved in order for the business to take position in the first place. Firstly, the organization has to attain a business or trade license from related authorities due the organization's location. The organization must be registered and recognized by the particular departments of government in food product. Secondly, the needs and demands of the customers are to be recognized in order to satisfy them. This will be achieved by producing high quality “roti jala” and curry that interest all parties. When these requirements are fulfilled, the organization can maximize the profits from the business and increase the number of customers. Thirdly, all the machineries, equipment and materials will be checked and re- checked to ensure no contamination on the goods and avoiding risk to customers' health when purchasing our organization's products. This is important not just for the purpose of gaining customer, but also in order to sustain the trust and existing numbers of customers. It is their rights according to the law to buy and purchase quality products from the providers, and must also be treated in a proper order.